The effect of parity on the proportion of important healthy fatty acids in raw milk of Holstein cows - Luděk Stádník; Jaromír Ducháček; Monika Okrouhlá; Martin Ptáček; Jan Beran; Roman Stupka; Lukáš Zita (Mljekarstvo)
The objective of this study was to determine and evaluate the effect of parity on the fatty acids groups’ proportion in Holstein cows’ milk during the first phase of lactations, with an emphasis on its potential importance for consumer health. A total of 25 Holstein cows, 9 primiparous, 9 in the 2nd, and 7 in the 3rd and subsequent parity, were observed and sampled at 7-day intervals through the first 17 weeks of lactation. The percentage proportion of saturated (hypercholesterolemic and volatile as its components) and unsaturated (monounsaturated and polyunsaturated as its components) fatty acids in the samples of milk fat (n=425) was determined. The effects of parity and negative energy balance, as well as regression, on the lactation week and the fat to protein ratio were evaluated using SAS 9.3. A significantly (P<0.01) lower proportion of unhealthy hypercholesterolemic fatty acids was detected in primiparous cows (-2.67 %) and those in the 3rd and subsequent lactation (-2.94 %) compared to the 2nd lactation, as well as a simultaneously higher proportion of healthy unsaturated fatty acids (+2.07, respectively +3.08 %). The determined relationships corresponded to organism stress evoked by the initiation of milk production and its maintenance in higher parities. Therefore, the generally required prolongation of dairy cows’ longevity can influence on the quality of raw milk, especially considering composition of fatty acids.